Influence of rs6667202 SNP on Interleukin-10 levels in the gingival fluid of patients with periodontitis grade C - Camila Schmidt Stolf; Tiago Taiete; Márcio Zaffalon Casati; Enílson Antônio Sallum; Francisco Humberto Nociti Júnior; Karina Gonzales Silvério Ruiz; RenatoCorrêa Viana Casarin (Universidade Estadual de Campinas, 2021)
Grade C periodontitis in youngers is characterized by a severe form of periodontitis, and IL10 rs6667202 single nucleotide polymorphism (SNP) has been described as an important feature in this disease etiology. Aim: This study aimed to evaluate, in vivo, the functionality of IL10 rs6667202 SNP on IL-10 gingival fluid levels. Methods: Thirty patients with Perio4C were selected, 15 with the IL10 AA genotype (rs6667202) and 15 with AC/CC genotypes. The gingival fluid was collected from two sites with probing depth ≥ 7 mm and bleeding on probing, and two healthy sites. The IL-10 concentration was determined by Luminex/MAGpix platform. Results: In deep pockets, the IL10 AA genotype presented a lower concentration of IL-10 when compared with AC or CC genotypes (p<0.05). In shallow pockets, no difference between groups was seen (p>0.05). Conclusion: IL10 rs6667202 SNP decreases the production of IL-10 in crevicular fluid, potentially affecting this disease progression.